Building Community Capacity in Village Fund Management: Implementation of the Public Administration Assistance Model in Rantau Pandan Village, Indonesia - Zulkifli, Zulkifli; M., Ariyanto; Sunaryo, Joko; Hamirul, Hamirul (Indonesian Community Empowerment Journal, 2024)
Village funds are one of the Indonesian government's programs to improve the development and welfare of village communities. However, complex village fund management often becomes an obstacle for village officials who have limited capacity. This community service aims to build the capacity of the Rantau Pandan Village community to manage village funds by implementing a public administration assistance model. This mentoring model includes training, mentoring, and monitoring and evaluation. The results of the activity show that the public administration assistance model is effective in increasing the knowledge, skills, and attitudes of village officials in managing village funds. This capacity building is expected to increase accountability and transparency in village fund management, as well as encourage more effective and efficient village development.